JUAL BELI TANPA LABEL HARGA DALAM PERSPEKTIF UNDANG UNDANG PERLINDUNGAN KONSUMEN - Alvina Damayanti; Ayu Anira (Jurnal At-Tabayyun, 2021)
This research aims to find out about the perspective of the consumer protection law regarding buying and selling without price tags. Buying and selling without price tags is buying and selling in which there is no price information in practice. This buying and selling phenomenon has become a habit in society. However, buying and selling like this also causes a lot of harm to consumers. Seeing the impact of the implementation of buying and selling without price tags, the researchers want to know how the point of view or perspective according to the consumer protection law. This research is qualitative descriptive, this study includes literature literature reviewing written sources through books and others as relevant reference sources. The object of this research is made to find out the impact received by consumers as a result of buying and selling without price tags. The data collection method uses observation, and collects appropriate data as a reference.